Trophic Plasticity of the Invasive Redbelly Tilapia (Coptodon zillii) in China Inferred From DNA Metabarcoding Analysis - Shoujie Tang; Ying Xing; Temesgen Tola Geletu; Jinliang Zhao (Ecology and Evolution, 2025)
ABSTRACT The redbelly tilapia (Coptodon zillii) is one of the most dangerous invasive alien fishes in the world. In order to better understand the feeding patterns of invasive populations in different habitats and seasons, and to reveal the possible force of differences in dietary composition among populations, we used DNA metabarcoding technology to analyze the dietary composition of 23 specimens from five different water bodies (two rivers and three reservoirs) in southern China, and 60 specimens from Shuikou Reservoir in four seasons (spring, summer, fall, and winter). The results showed that samples from five different water bodies and four seasons in Shuikou Reservoir were annotated to a total of 22 and 37 phyla of food categories, respectively. Generalist trophic strategies were dominant in C. zillii populations. There was significant spatial heterogeneity in the diet composition, with higher levels of trophic diversity in riverine populations. Water temperature, dissolved oxygen, and conductivity were important environmental factors driving changes in prey taxa of populations from different habitats. The dietary composition of populations in Shuikou Reservoir showed significant seasonal heterogeneity, with summer being the season with the highest level of trophic diversity. Total nitrogen, turbidity degree, pH, and permanganate index were the important environmental factors driving the prey taxa changes of populations in different seasons of Shuikou Reservoir. Our results indicated that C. zillii are omnivorous; they have a wide range of recipes in both rivers and reservoirs in southern China, and show high trophic plasticity in different habitats and at different seasons of the year.